2021
DOI: 10.3389/fmicb.2021.675597
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Typing Increases the Discriminatory Power of Streptococcus agalactiae Typing Methods

Abstract: We explored the relevance of a Clustered regularly interspaced short palindromic repeats (CRISPR)-based genotyping tool for Streptococcus agalactiae typing and we compared this method to current molecular methods [multi locus sequence typing (MLST) and capsular typing]. To this effect, we developed two CRISPR marker schemes (using 94 or 25 markers, respectively). Among the 255 S. agalactiae isolates tested, 229 CRISPR profiles were obtained. The 94 and 25 markers made it possible to efficiently separate isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In addition, this review shows that, especially in streptococci but also in other bacteria, sequencing CRISPR loci is also a relatively easy way to characterize and classify isolates precisely. Indeed, many studies have demonstrated that using CRISPR as a typing method is a promising tool and must be developed (Pourcel et al, 2005;Brudey et al, 2006;Beauruelle et al, 2021). More than precisely classifying strains, it can give a lot of information about species evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this review shows that, especially in streptococci but also in other bacteria, sequencing CRISPR loci is also a relatively easy way to characterize and classify isolates precisely. Indeed, many studies have demonstrated that using CRISPR as a typing method is a promising tool and must be developed (Pourcel et al, 2005;Brudey et al, 2006;Beauruelle et al, 2021). More than precisely classifying strains, it can give a lot of information about species evolution.…”
Section: Discussionmentioning
confidence: 99%
“…MLST is the current reference method used to distinguish S. agalactiae isolates, and more than 1,600 different sequence types (ST) are now described. This method has a good discriminating power but, with the discovery and research on CRISPR-Cas systems, recent studies propose CRISPR-typing as a promising alternative method (Beauruelle et al, 2017(Beauruelle et al, , 2021.…”
Section: Streptococcus Agalactiaementioning
confidence: 99%
“…In GBS research, the native CRISPR-Cas9 system has become a focus of study and the basis of new tools for pathogenesis research, such as using the highly variable CRISPR array as a strain-level barcode for lineage tracking in models of disease 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…This same study showed that, as in GAS, the GBS Cas9 enzyme requires a NGG PAM next to the target recognition site at its 3′ end 28 . Subsequent work has further investigated lineage specificity of GBS CRISPR arrays and their use as barcodes for precision subtyping 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Beauruelle et al explored the relevance of the CRISPR-based genotyping tool for GBS typing and compared it to current molecular methods, including MLST, by analyzing 255 GBS isolates. The authors demonstrated that the analysis of leader-end spacers, which vary more widely between strains, may offer stronger discriminating power than MLST ( 31 ). According to these data and previous studies, CRISPR1 typing has been proposed as a reference method for GBS typing ( 31 ).…”
Section: Introductionmentioning
confidence: 99%